ALIX and TSG101 are essential for cellular entry and replication of two porcine alphacoronaviruses. - Xiongnan Chen; Yifan Liang; Zhijun Weng; Chen Hu; Yunzhao Peng; Yingshuo Sun; Qi Gao; Zhao Huang; Shengqiu Tang; Lang Gong; Guihong Zhang (PLoS Pathogens, 2024)
Alphacoronaviruses are the primary coronaviruses responsible for causing severe economic losses in the pig industry with the potential to cause human outbreaks. Currently, extensive studies have reported the essential role of endosomal sorting and transport complexes (ESCRT) in the life cycle of enveloped viruses. However, very little information is available about which ESCRT components are crucial for alphacoronaviruses infection. By using RNA interference in combination with Co-immunoprecipitation, as well as fluorescence and electron microscopy approaches, we have dissected the role of ALIX and TSG101 for two porcine alphacoronavirus cellular entry and replication. Results show that infection by two porcine alphacoronaviruses, including porcine epidemic diarrhea virus (PEDV) and porcine enteric alphacoronavirus (PEAV), is dramatically decreased in ALIX- or TSG101-depleted cells. Furthermore, PEDV entry significantly increases the interaction of ALIX with caveolin-1 (CAV1) and RAB7, which are crucial for viral endocytosis and lysosomal transport, however, does not require TSG101. Interestingly, PEAV not only relies on ALIX to regulate viral endocytosis and lysosomal transport, but also requires TSG101 to regulate macropinocytosis. Besides, ALIX and TSG101 are recruited to the replication sites of PEDV and PEAV where they become localized within the endoplasmic reticulum and virus-induced double-membrane vesicles. PEDV and PEAV replication were significantly inhibited by depletion of ALIX and TSG101 in Vero cells or primary jejunal epithelial cells, indicating that ALIX and TSG101 are crucial for PEDV and PEAV replication. Collectively, these data highlight the dual role of ALIX and TSG101 in the entry and replication of two porcine alphacoronaviruses. Thus, ESCRT proteins could serve as therapeutic targets against two porcine alphacoronaviruses infection.